Continuity of post-stroke care from hospital to home - Tegrado, Lindsay Allen R.; Saavedra, Apryll Raedine B.; Sereneo, Kate Anjelyn; Soriano, Thea Angelica P.; Torres, Paola Anne P.; Tureda, Revi C.; Velina, Athena Zea Marie M.
Background of the Study